OPTIMASI ALIRAN PADA JARINGAN DENGAN ALGORITMA SUCCESSIVE SHORTEST PATH - Khoirum muslimah; Siti Khabibah (Jurnal Matematika, 2012)
Optimization is a process flow to achieve the ideal (the effective value can be achieved) of an object traveling from one place to another within a network. Transportation problems are part of the linear program is usually completed by the usual simplex method. While the transport network is a visualization of the transportation problem into a graph problem. At this final project method or algorithm used in obtaining optimal flow is the successive shortest path algorithm. The first is to find the shortest path of the transport network. The second is to choose a node  with a value of supply  (before supply is applied to some demand) and the node  with the demand . The third is to calculate , with arc on shortest path  to . Then send  units of flow from node  to node  along the shortest path in the residual network. At the end of the optimal flow will be obtained, if the condition residual value  does not negative of all the arcs in the residual network and  value for all . Key words: successive shortest path, the optimization of flow, transport networks